Perencanaan Strategi Media Sosial Akun Instagram @mataharikeci_id oleh Komunitas Mataharikecil - Amar Shiddiq Junaidi; Hanny Hafiar; Anwar Sani (Expose: Jurnal Ilmu Komunikasi, 2022)
Technology plays an important role in today's society. Technology has changed the society not only in the way it communicates but also in the attitudes and relationships with people of all ages who live in it both positively and negatively. Matahari Kecil Indonesia is a non-profit organization that focuses on social issues to help underprivileged families achieve education for their children and become economically independent. In the process, Matahari Kecil Indonesia utilizes social media Instagram to help achieve organizational goals. Instagram social media, in this case, is a photo and video sharing platform with a variety of features and functions. This research is a descriptive qualitative study that focuses on knowing the process of planning social media strategies for @mataharikecil_id as a source of accurate information about organization’s education and social activities. This study aims to answer the identification of problems regarding social media strategy planning using the POST Method. The results of this study reveal that the ‘people’ stage consists of public segmentation, understanding the public, and analyzing the public. The ‘objective’ stage is the application of the SMART method in the process of setting organizational goals. Then, the ‘strategy’ stage reveals that the content production strategy begins with the planning stage which is followed by production and execution. After the concepts and data regarding public behavior are collected, then the content production process can be carried out involving creative people to produce visually attractive content. At last, the combination of technologies chosen are Instagram, WhatsApp, Line, and e-mail.